A Modified Compound From Paeoniflorin, CP-25, Suppressed Immune Responses and Synovium Inflammation in Collagen-Induced Arthritis Mice - Chen, Jingyu; Wang, Ying; Wu, Huaxun; Yan, Shangxue; Chang, Yan; Wei, Wei (Frontiers in Pharmacology, 2018)
Paeoniflorin-6ʹ-O-benzene sulfonate (CP-25) is a modified paeoniflorin, which is the main bioactive component of total glucosides of peony. This study evaluated the anti-inflammatory and immunoregulatory effects of CP-25 in mice with collagen-induced arthritis (CIA) and the potential mechanisms underlying these effects. After the onset of CIA, mice were given CP-25 (17.5, 35, or 70 mg/kg) or methotrexate (MTX, 2.0 mg/kg). The arthritis index, swollen joint count, and joint and spleen histopathology were evaluated. T and B cell subsets were assayed using flow cytometry, while the proliferation of these cells and fibroblast-like synoviocytes (FLS) were evaluated using the Cell Counting Kit-8. β2-adrenoceptor (β2-AR) expression was assayed using flow cytometry, immunohistochemistry, and western blotting. FLS migration and invasion were assayed using Transwells. CP-25 (35 or 70 mg/kg) attenuated the arthritis index and swollen joint count, alleviated joint and spleen histopathology, suppressed excessive T cell activation, and attenuated humoral immunity in CIA mice. CP-25 increased β2-AR expression on T cells, B cells, dendritic cells, and the synovium in CIA mice. CP-25 up-regulated the β2-AR agonist response and attenuated FLS activation; these effects may reflect CP-25-mediated reduction of β2-AR desensitization due to down-regulation of membrane G protein-coupled receptor kinase 2 expression. These results suggest that CP-25 suppressed immune responses and synovium inflammation in mice with CIA, effects that were associated with reduced β2-AR desensitization and the promotion of β2-AR signaling.